2010
DOI: 10.1111/j.1469-185x.2010.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Having sex, yes, but with whom? Inferences from fungi on the evolution of anisogamy and mating types

Abstract: The advantage of sex has been among the most debated issues in biology. Surprisingly, the question of why sexual reproduction generally requires the combination of distinct gamete classes, such as small and large gametes, or gametes with different mating types, has been much less investigated. Why do systems with alternative gamete classes (i.e. systems with either anisogamy or mating types or both) appear even though they restrict the probability of finding a compatible mating partner? Why does the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
286
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(290 citation statements)
references
References 192 publications
2
286
0
2
Order By: Relevance
“…One possibility is that the extremely low heterozygosity found in E. cuniculi is the result of self-reproduction (selfing), a mechanism that is known to heavily reduce the amount of heterozygosity in many other vertebrate parasites (22,34,35,40) and to produce clones that are optimally adapted to certain hosts (i.e., highly homozygous individuals) but that can still maintain the capacity to undergo outcrossing and create new variation following rare changes in environmental conditions (i.e., opportunistic sexuals). However, given the source of the E. cuniculi strains we have analyzed, the extreme reduction in heterozygosity we have observed may have been exacerbated by the methodology used to originate and propagate these strains under laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that the extremely low heterozygosity found in E. cuniculi is the result of self-reproduction (selfing), a mechanism that is known to heavily reduce the amount of heterozygosity in many other vertebrate parasites (22,34,35,40) and to produce clones that are optimally adapted to certain hosts (i.e., highly homozygous individuals) but that can still maintain the capacity to undergo outcrossing and create new variation following rare changes in environmental conditions (i.e., opportunistic sexuals). However, given the source of the E. cuniculi strains we have analyzed, the extreme reduction in heterozygosity we have observed may have been exacerbated by the methodology used to originate and propagate these strains under laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Following vegetative growth and if the environmental conditions are favorable, the dikaryotic mycelia can produce fruit bodies. In this process, a crucial factor is the mating compatibility between monokaryons (Moore and Frazer 2002; Billiard et al 2011). For monokaryotic cells, even if they belong to the same species and are located in the same community close to each other, they can only mate and form fertile mycelia when they have different alleles at the mating type locus (loci) (Casselton and Olesnicky 1998; Moore and Frazer 2002; Billiard et al 2011).…”
Section: Emerging Directionsmentioning
confidence: 99%
“…It is thus not surprising that recent advances in genome sequencing have revealed that most fungal species have retained the machinery for sexual reproduction and meiosis (Halary et al 2011;Dyer and O'Gorman 2012;Gioti et al 2013;Heitman et al 2014). However, this resilience to keep sexual competence intact comes with an extremely dynamic evolution of sexual behaviors and mating type-determining mechanisms, which may influence important evolutionary and ecological processes, such as adaptation and speciation (Billiard et al 2011;Heitman et al 2013;Nieuwenhuis et al 2013).In the phylum Basidiomycota, sexual reproduction is often dictated by two independent sets of mating-type (MAT)-specific genes that control different stages of the sexual cycle. These genes encode premating lipopeptide pheromones and their cognate receptors (P/R), which mediate recognition of mating partners and cell fusion, and homeodomain transcription factors (HD1 and HD2) that form heterodimers that regulate postmating behavior (Kües et al 2011;Nieuwenhuis et al 2013).…”
mentioning
confidence: 99%
“…It is thus not surprising that recent advances in genome sequencing have revealed that most fungal species have retained the machinery for sexual reproduction and meiosis (Halary et al 2011;Dyer and O'Gorman 2012;Gioti et al 2013;Heitman et al 2014). However, this resilience to keep sexual competence intact comes with an extremely dynamic evolution of sexual behaviors and mating type-determining mechanisms, which may influence important evolutionary and ecological processes, such as adaptation and speciation (Billiard et al 2011;Heitman et al 2013;Nieuwenhuis et al 2013).…”
mentioning
confidence: 99%